FORCE ANALYSIS OF THE OPERATIONAL TAJAK BEDANDAN AS A BASIS FOR THE DEVELOPMENT OF LOCAL AGRICULTURAL MACHINERY - Dewi, Indya; Rahmi, Alia; Hardarani, Nofia (Agroscientiae, 2014)
Tajak that has been used for hundreds of years by traditional local farmers in South Kalimantan has shownÂ its excellence. It is the appropriate tool to be used on agricultural land that has a typology of swamp land.Â The difficulty of the operation, the amount of power needed to operate and a decline in interest in theÂ younger generation to work in agriculture demanded a call for this tool under research for improvement. ByÂ analyzing the forces acting on tajak, its operational principles will be obtained. This information is useful as aÂ reference for the procedure of t ools utilization in swamp land preparation accordingly with the local wisdom.Â It may promote a correct tajak operation procedure, hence reducing the workload and the number ofÂ occupational accidents, and also important in designing an ergonomic, effective and efficient tajak. In theÂ long run, this research is expected to be the basis for developing tajak as local knowledge -based agriculturalÂ machinery of the Banjarese society in South Kalimantan. The research was conducted following these steps:site selection, land preparation, operator selection, data recording and data processing/analysis. The resultÂ showed that the pattern of tajak operational motion is uniform, with the cutting direction to the left and theoperatorâs left hand plays an important role a s the ârudderâ. Tajak mass and the lift angle affect the magnitudeÂ of force acting on tajak with the maximum force at the minimum axial force. The maximum force experiencedÂ by tajak is at the shaft end and decreases toward the eye.